THE DIALOG „GOVERNANCE – SOCIETY” IS A NECESSARY CONDITION FOR DEMOCRATIC REFORMS IN MODERN UKRAINE - Довбня, О.М.; Довбня, О.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The questions of the interdependence of democratic transformations in modern Ukraine, and the need to create an effective system of control by the organized society over the activities of government agencies are considered . Some directions for creation of such mechanism and for increase of civic participation of the population are suggested.